Digital Marketing Communication Strategy Based on STP and 4C: An Interdisciplinary Communication Approach to Non-Formal Education in Bone Regency - Nur Khazizah M; Muhammad Fachrul Salam; Andi Jamiati Paramita (INJECT (Interdisciplinary Journal of Communication), 2026)
The rapid evolution of new media and information technology has fundamentally restructured public communication patterns, necessitating a paradigm shift in the communication strategies of educational institutions. While digital marketing communication is widely documented in the commercial and formal schooling spheres, its application through an interdisciplinary communication lens in non-formal educational institutions remains very limited. This study evaluates the implementation of a digital marketing communication strategy that integrates media communication and social interaction studies for the Mawar Community Learning Center (PKBM) in Bone Regency. Using a descriptive cross-sectional design incorporating a retrospective pre-test component, data were drawn from 101 respondents. The STP (Segmentation, Targeting, Positioning) framework was applied to map the message architecture and media preferences of the audience, revealing that the primary audience is females (22–35 years old) who are highly receptive to visual message transmission in the form of short videos on Instagram and TikTok. Furthermore, the 4Cs (Context, Communication, Collaboration, Connection) framework was used to assess the effectiveness of the communication dialogue and post-campaign public perception. The results of the study indicate a substantial shift in information penetration, moving from 54.5% retrospective awareness to 98% current awareness. Furthermore, this new media communication strategy effectively expanded the geographical transmission of messages, reaching 47.5% of the audience outside the host sub-district. The 4C analysis yielded a highly favorable message reception rate, particularly in fostering emotional connections and supportive community communication (the Total Category Response score for the Connection dimension reached 91.29%). Despite methodological limitations, these findings enrich the interdisciplinary communication science discourse by demonstrating that dialogic and contextualized digital media communication management can significantly bridge information asymmetries, dismantle institutional stigma, and reconstruct public trust in alternative educational institutions.